ANALYSIS OF CULTURAL ADAPTATION STRATEGIES AND READABILITY IN RESIDENT EVIL 9 CUT-SCENE SUBTITLES ON MiawAug - Jenita Barus (Ma Chung Press, 2026)
Subtitle translation in audiovisual media serves not only to convey the language from the source language to the target language, but also to adapt cultural elements and ensure the text’s readability for the audience. In the context of video games, subtitle readability is crucial because both players and viewers reading the subtitles must understand dialogue quickly without disrupting the gaming experience. This study aims to analyze strategies for cultural adaptation and subtitle readability in the cutscenes of the video game Resident Evil 9: Requiem, translated from English to Indonesian. This study employs a descriptive qualitative design, using subtitle data from the MiawAug YouTube Channel, specifically unofficial subtitles by the BROMAX translator community. The study population is the video game Resident Evil 9: Requiem. The sample was selected purposively from cutscene subtitles containing character dialog that include cultural elements and aspects of readability. Data were collected through observation and documentation, then analyzed by classifying cultural adaptation strategies and assessing subtitle readability based on clarity, fluency, and contextual appropriateness. The results confirm that appropriate cultural adaptation strategies significantly enhance subtitle readability, clarity, and fluency for Indonesian viewers. This study concludes that a balance between cultural adaptation and readability is a key factor in the success of audiovisual subtitle translation for video games. Keywords: audiovisual translation, cultural adaptation strategies, readability, subtitling, video game.